Pengaruh Lingkungan Kerja Fisik dan Budaya Kerja terhadap Kinerja Karyawan pada PT. Cakrabuana Consultants Jakarta Selatan - Veritia, Veritia; Hayati, Feb Amni; Sularmi, Lili; Romadhon, Reza Sofyan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The urgency of this research lies in the growing recognition that both the physical work environment and organizational culture significantly impact employee performance, especially in increasingly competitive business landscapes. This study aims to examine the influence of the physical work environment and work culture on employee performance at PT. Cakrabuana Consultants, South Jakarta. Using a quantitative observational method, data were collected from 80 employees and analyzed through multiple linear regression with the assistance of SPSS version 26. The findings reveal that both the physical work environment and work culture independently and collectively have a significant positive effect on employee performance. A conducive physical work environment enhances comfort, focus, and motivation, while a strong, supportive work culture fosters engagement, discipline, and collaboration. The analysis suggests that improving both factors can lead to a meaningful increase in employee productivity and effectiveness. These results underline the importance for organizations to invest in physical workspace improvements and cultivate a positive, performance-oriented culture. Such efforts can lead not only to better individual outcomes but also to enhanced organizational success. The implications highlight that management should prioritize workplace conditions and cultural development as strategic assets in human resource management.